Sending Money Home – Maintaining Family And Community - Singh, Supriya (Penerbit Universiti Sains Malaysia (USM Press), 2007)
Remittances, that is, money migrants send home, are more than double the official aid received by developing countries. International financial institutions and national governments have focused on the growth of remittances, their impact on poverty alleviation and development. In this paper I present a complementary picture from the perspective of the migrants who send money home. I draw on an ongoing qualitative project of family, money and migration in the Indian Diaspora. Migrants send money home because they want to continue to remain part of their families and communities back home. Remittances display this family and community identity to themselves and to others. Remittances thus are family and community threads that intersect across countries in an increasingly global world.